ANALYSIS OF SPATIAL DISTRIBUTION AND TEMPORAL TREND OF REFERENCE EVAPOTRANSPIRATION AND PAN EVAPORATION IN CHANGJIANG (YANGTZE RIVER) CATCHMENT - Xu C.-y.; Jiang T.; Gong L.; Chen D.; Singh V.P. (My University, 2006)
In this study the Penman-Monteith reference evapotranspiration, pan evaporation measured by a 20 cm pan, and pan coefficient, i.e., the ratio of Penman-Monteith evapotranspiration to pan evaporation, at 150 meteorological stations during 1960-2000 in the Changjiang (Yangtze River) catchment in China are calculated, compared and regionally mapped. Their spatial distributions and temporal variations are examined and the causes for the variations are discussed. The spatial distributions of temporal trends in the reference evapotranspiration as well as in the meteorological variables that determine evapotranspiration are analyzed. The contributions of various meteorological variables to the temporal trend detected in the reference evapotranspiration and pan evaporation are then determined. The results show that: (1) the spatial distributions of reference evapotranspiration and pan evaporation are roughly similar. Spatial correlation coefficients between the reference evapotranspiration and the pan evaporation are high for both the seasonal and annual values. The temporal correlation between the two estimates is higher in the lower (humid) region than in the upper (semi-arid) region. The spatial distribution pattern of the pan coefficient is significantly influenced by wind speed and relative humidity in the region. Higher values of the pan coefficient were found in the central area of the catchment with a relatively high humidity (as compared with the upper area) and a very low wind speed (as compared with other areas); (2) for the whole catchment, there is a significant decreasing trend in both the reference evapotranspiration and the pan evaporation, which is mainly caused by a significant decrease in the net total radiation and to a lesser extent by a significant decrease in the wind speed over the catchment. No temporal trend is detected for the pan coefficient; (3) sensitivity analysis shows that the reference evapotranspiration is most sensitive to the net total radiation, followed by relative humidity, air temperature and wind speed. © 2005 Elsevier B.V. All rights reserved.
Keywords: CHANGJINAG CATCHMENT; CHINA; PAN EVAPORATION; PENMAN-MONTEITH METHOD; REFERENCE EVAPOTRANSPIRATION; TREND ANALYSIS